STRATEGI MEDIA RELATIONS PT JIEXPO DALAM MENGELOLA PUBLISITAS JAKARTA FAIR KEMAYORAN 2025 - Nadia Tabina; Centurion Chandratama Priyatna; Hanny Hafiar (Konvergensi, 2026)
Organizing large-scale events requires a media relations strategy capable of managing the dissemination of information to the public. PT Jakarta International Expo (JIExpo), as the organizer of the 2025 Jakarta Fair Kemayoran, faces the need to manage publicity for one of the largest multi-product exhibitions in Indonesia. However, high media exposure also presents challenges, specifically the emergence of various negative coverages regarding field operations and public facilities. This study aims to examine PT JIExpo’s media relations strategies in managing publicity for Jakarta Fair Kemayoran 2025 through the aspects of managing relationships, developing strategies, and building networks. This study utilizes a descriptive qualitative approach. Data were collected through in-depth interviews with six internal informants from PT JIExpo's Media Center division and two national media journalists, complemented by field observations and literature reviews. The results indicate that PT JIExpo implements a media relations strategy by managing relationships with the media through intensive communication, personal approaches, and serving journalists' needs. Strategy development is executed through providing publicity materials, distributing press releases, and handling negative coverage through issue analysis and clarifications, although crisis communication planning remains reactive. Network development is conducted through media data collection, media verification, and relationships with journalistic organizations. The study concludes that PT JIExpo's media relations strategy has supported publicity management, yet certain aspects require strengthening, particularly in crisis communication planning, information management, and professional network expansion. This study recommends strengthening proactive crisis communication planning, implementing more balanced media information access management, and expanding professional networks through relevant organizations.